Cloaca in Discordant Monoamniotic Twins: Prenatal Diagnosis and Consequence for Fetal Lung Development - Yvon Chitrit; Edith Vuillard; Sunavy Khung; Nadia Belarbi; Fabien Guimiot; Francoise Muller; Alaa El Ghoneimi; Jean Francois Oury (Thieme Medical Publishers, Inc., 2014)
Abstract Objective Describe a case of cloaca prenatally diagnosed in one of a set of monoamniotic twins. Study Design Retrospective review of a case. Results Cloaca is one of the most complex and severe degrees of anorectal malformations in girls. We present a discordant cloaca in monoamniotic twins. Fetal ultrasound showed a female fetus with a pelvic midline cystic mass, a phallus-like structure, a probable anorectal atresia with absence of anal dimple and a flat perineum, and renal anomalies. The diagnosis was confirmed by fetal magnetic resonance imaging postnatally. Conclusions The rarity of the malformation in a monoamniotic pregnancy, the difficulties of prenatal diagnosis, the pathogenic assumptions, and the consequences of adequate amniotic fluid for fetal lung development are discussed.